Pharmacy student decision making in over-the-counter medicine supply: a critical incident study. - McMillan, Sara S.; Thagarajah, Thachaayini; Anderson, Claire; Kelly, Fiona (Elsevier, 2017)
Background: Various factors influence decision making in over-the-counter (OTC) medicine consultations, yet limited studies have focused, in-depth, on the thought process of pharmacy staff. This includes pharmacy students as pharmacists-in-training. Aim: To explore the factors that influence pharmacy students’ decisions in relation to OTC consultations and choice of OTC medicine/s. Methods: Semi-structured interviews using the critical incident technique were undertaken with ten pharmacy students in Australia, who also worked as part-time pharmacy staff. Results: Nine key themes were identified to influence pharmacy student decision making in OTC consultations, including customer response, confidence and scope of practice. Product requests were reported as more challenging due to customer expectations and experiences in other pharmacies, states or countries. Although negative customer response influenced some students to supply medicines in contradiction of evidence, an overarching concern for safety meant that a medicine was only supplied if unlikely to cause harm. Students reported developing confidence in OTC decision making more from real-life practice than university training; greater confidence was identified for inquiries more frequently experienced in the pharmacy. Students perceived that customers had assumptions around support staff, and were happier to talk to students than assistants. Conclusion: This study further identified that OTC decision making is a complex process for pharmacy students. Additional opportunities for experiential learning within this area are suggested, such as work-based placements or in-class activities such as role-plays with simulated patients.